Testosterone Promotes an Anabolic Increase in the Rat Female Prostate (Skene's Paraurethral Gland) Which Acquires a Male Ventral Prostate Phenotype - Biancardi, Manoel F.; Santos, Fernanda C. A.; Madi-Ravazzi, Liliam [UNESP]; Goes, Rejane M. [UNESP]; Vilamaior, Patricia S. L.; Felisbino, Sergio L. [UNESP]; Taboga, Sebastiao R. [UNESP] (Wiley-Blackwell, 2010)
The female prostate (Skene's paraurethral gland) in the rat is morphologically similar to the ventral lobe of male adults and has been described in other rodent species and humans. Previous studies on prostate morphogenesis suggest that female Wistar rats (Rattus norvegicus) do not develop this gland due to the absence of testosterone during the embryonic and neonatal periods. on the other hand, studies conducted in our laboratory have shown that some females of this species can present an undeveloped but functional prostate. Recent studies on this gland have caused scientific interest because, besides being active in the processes of synthesis and secretion of prostatic material, it is also targeted by both malignant and benign lesions, mainly during senescence. Thus, this work aims to evaluate the structure of female prostate of adult rats (Rattus norvegicus) under normal conditions and under the effect of testosterone treatment and carry out comparative studies on the ventral prostate of young and adult male rats. Morphological and morphometric stereological analyses and immunocytochemical and ultrastructural studies were conducted. The results have shown that the prostate gland of rats exposed to androgen therapy have experienced intense growth, becoming more active in relation to synthesis and secretion. It may be concluded that the prostate in control adult female rats is morphologically very similar to the prostatic ventral lobe of young male rats. Besides, under androgenic action, the female prostate grows considerably and becomes similar to the prostatic ventral lobe in male adults. Anat Rec, 293:2163-2175, 2010. (C) 2010 Wiley-Liss, Inc.
Keywords: female prostate; ventral male prostate; androgens; rat; morphology